Penyelesaian Sengketa Tanah antara Masyarakat Kelurahan Betara Kiri dengan Pihak Perusahaan Melalui Mediasi - Mayang Hamidah, Siti; Alissa, Evalina; Manik, Herlina (Zaaken: Journal of Civil and Business Law, 2025)
Land disputes remain a persistent problem in Indonesia due to increasing land demand and weak law enforcement. Previous studies often emphasize litigation, while research on the effectiveness of mediation in local land conflicts is still limited. This study addresses that gap by examining the land dispute between the community of Kelurahan Betara Kiri and a private company in Tanjung Jabung Barat Regency, Jambi Province. The objective is to analyze the mediation process as an alternative dispute resolution mechanism and to identify the main obstacles to its effectiveness. Using an empirical legal approach, the study finds that mediation has been attempted repeatedly since 2018, involving local government, the Forestry Service, and law enforcement agencies. However, the process has not been effective due to persistent disagreements over land ownership interpretation, breach of partnership agreements, leadership dualism within farmer groups, and weak compliance with mediation outcomes. The contribution of this research lies in demonstrating how the combination of unclear land tenure arrangements, institutional weaknesses, and low community legal awareness undermines mediation as a settlement tool. The findings highlight the need for stronger legal certainty, more transparent facilitation, and firmer enforcement to enhance the role of mediation in resolving agrarian conflicts in Indonesia.